Gene-gene interactions in the NAMPT pathway, plasma visfatin/NAMPT levels, and antihypertensive therapy responsiveness in hypertensive disorders of pregnancy - Luizon, M. R.; Palei, A. C.T.; Belo, V. A.; Amaral, L. M.; Lacchini, R.; Duarte, G.; Cavalli, R. C.; Sandrim, V. C. [UNESP]; Tanus-Santos, J. E. (Springer Nature, 2017)
Nicotinamide phosphorybosil transferase (NAMPT) polymorphisms affect visfatin/NAMPT levels and may affect the responsiveness to therapy in hypertensive disorders of pregnancy. We examined whether NAMPT polymorphisms (rs1319501 T>C and rs3801266 A>G), or haplotypes, and gene-gene interactions in the NAMPT pathway affect plasma visfatin/NAMPT levels and the response to antihypertensive therapy in 205 patients with preeclampsia (PE) and 174 patients with gestational hypertension. We also studied 207 healthy pregnant controls. Plasma visfatin/NAMPT levels were measured by ELISA. Non-responsive PE patients with the TC+CC genotypes for the rs1319501 T>C, and with the AG+GG genotypes for the rs3801266 A>G polymorphism had lower and higher visfatin/NAMPT levels, respectively. The ' C, A' haplotype was associated with response to antihypertensive therapy, and with lower visfatin/NAMPT levels in PE. Interactions among NAMPT, TIMP-1 and MMP-2 genotypes were associated with PE and with lack of response to antihypertensive therapy in PE. Our results suggest that NAMPT polymorphisms affect plasma visfatin/NAMPT levels in nonresponsive PE patients, and that gene-gene interactions in the NAMPT pathway not only promote PE but also decrease the response to antihypertensive therapy in PE.